mRNA Expression of PITX3 gene in Congenital Cataract Caused by Rubella Virus Infection - Marlyanti Nur Rahmah Akib1,2 , Budu3 , Habibah S Muhiddin4, Andi Muhammad Ichsan4, Ratih Natasha Mah (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: To analyze mRNA expression of PITX3 gene in congenital cataract caused by rubella virusinfectionMethods: Patients under the age of 18 who were diagnosed with congenital cataracts, were tested for antirubella antibodies, toxoplasma and cytomegalovirus and then underwent cataract surgery, and lens capsuleand lens mass samples were taken. Samples taken will be examined for mutation and expression of thePITX3 mRNA gene.Results: 15 eye samples were included in the study. there was no relationship with rubella infection withPITX-3 gene mRNA expression in the capsule sample and lens mass (p> 0.05). However, in terms ofaverage PITX-3 mRNA gene expression was found to be higher in rubella infection compared to non-rubellainfection. Based on the examination site, there was no significant difference in expression of PITX-3 mRNAgene between the lens capsule sample and the lens mass (p> 0.05). Although there was no statisticallysignificant difference, in terms of the average, the PITX-3 Gen mRNA expression was found to be higher inthe lens capsule compared to the lens mass.Conclusions: Rubella virus infection was the most common cause in the sample, which indicated the needfor prevention of rubella infection in pregnant women to reduce the adverse effects of rubella virus infection.PITX3 gene mRNA expression was higher in the Rubella infection group, indicating the possible role of thePITX3 gene in the pathogenesis of congenital cataracts due to rubella virus infection. The average mRNAexpression of the PITX3 gene is higher in the lens capsule compared to the lens mass although it does notsignificantly indicate the important role of the gene in the process of regulating epithelial cells and lensequatorials.